The Discovery of Natural Miscanthus Accessions Related to Miscanthus × giganteus Using Chloroplast DNA. Issue 4 (1st July 2014) - Feng, X.P.; Lourgant, K.; Castric, V.; Saumitou‐Laprade, P.; Zheng, B.S.; Jiang, D.; Brancourt‐Hulmel, M.
ABSTRACT: It is essential to enlarge the pool of varieties of the biomass crop Miscanthus to support the increase in its cultivation area, and several natural species from eastern or southeastern Asia could be of interest. Our main study objectives were: (i) to investigate the frequency spectrum of the haplotypes of natural Chinese accessions and their geographic distribution in China, and (ii) to identify the Chinese chloroplast genomes related to the maternal genomes of cultivated European varieties. We studied 21 clones cultivated in Europe and 44 wild Chinese accessions from 10 Chinese provinces covering four species of Miscanthus : M. sacchariflorus (Maxim.) Hack., M. sinensis Andersson, M. floridulus (Labill.) Warb. ex K. Schum. & Lauterb., and M . × giganteus J.M. Greef & Deuter ex Hodkinson & Renvoize. We used chloroplast DNA from sugarcane ( Saccharum officinarum L.) due to its taxonomic relationship with Miscanthus and designed primers using the large single‐copy region of the chloroplast genome. The polymorphisms belonged to noncoding and coding regions and were substitutions that corresponded to single nucleotide polymorphisms. Haplotypes were then determined, enabling the investigation of the haplotype frequency spectrum and the geographic distribution of the accessions in China. Furthermore, the maternal genome of M . × giganteus appears related to some Chinese M. sacchariflorus clones. The corresponding geographic native area of these wild clones could be of interest to enlarge the genetic variability for the breeding of new interspecific hybrids.